High Resolution Time-domain Induced Polarization Tomography with Merging Data Levels by Two Different Optimized Arrays for Slope Monitoring Study - Bery, Andy Anderson; Saad, Rosli (Mete Oner, 2013)
High Resolution Time-domain Induced Polarization Tomography with Merging Data Levels by Two Different Optimized Arrays for Slope Monitoring Study